A preparation method of a carbon nanofiber catalyst loaded with a non-noble metal high-entropy alloy in situ

CN122907656APending Publication Date: 2026-10-13FUJIAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611068755.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

尽管上述研究充分证明了高熵合金催化剂在Li-CO2电池中的优越性能,但目前所报道的高熵合金组分中普遍含有Ru、Ir等贵金属元素,催化剂成本依然较高,难以满足大规模实际应用的需求

Benefits of technology

[0016]本发明将静电纺丝原位制备技术用于负载非贵金属高熵合金的碳纳米纤维自支撑正极催化剂,提供了一种高性能锂-二氧化碳电池正极材料。该材料具有以下优势:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907656A_ABST
    Figure CN122907656A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a carbon nanofiber high-efficiency catalyst in-situ loaded with a non-noble metal high-entropy alloy, which comprises the following steps: dissolving iron acetate, cobalt acetate, nickel formate, copper chloride and indium chloride in N,N'-dimethylformamide, adding polyacrylonitrile and stirring uniformly to prepare a spinning slurry; preparing a FeCoNiCuIn@PAN precursor film by using an electrostatic spinning technology; and through segmented heat preservation pre-oxidation and high-temperature carbonization treatment under an Ar / H2 mixed atmosphere, generating a carbon nanofiber self-supporting positive electrode material in-situ loaded with a uniform high-entropy alloy of iron, cobalt, nickel, copper and indium. The application has the advantages that the preparation process is simple and controllable, the obtained self-supporting positive electrode material does not need to be additionally added with a conductive agent and a binder, high-entropy alloy nanoparticles are uniformly dispersed, catalytic active sites are rich, and when used as a lithium-carbon dioxide battery positive electrode, the self-supporting positive electrode material can effectively reduce a charge-discharge overpotential, and improve the rate performance and cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-carbon dioxide battery materials technology. More specifically, it relates to a method for preparing non-precious metal high-entropy alloy carbon nanofiber materials for lithium-carbon dioxide battery cathode materials based on electrospinning technology in situ loading. Background Technology

[0002] With the continued consumption of fossil fuels and the increasing emissions of the greenhouse gas CO2, the development of electrochemical energy storage systems that combine CO2 fixation and high-density energy storage has become an urgent priority. Lithium-carbon dioxide (Li-CO2) batteries, due to their high theoretical energy density (1876 Wh / kg), are a promising candidate. -1 With its high theoretical discharge potential (approximately 2.8 V), Li-CO2 batteries are considered a key candidate system for next-generation high-performance energy storage devices, enabling efficient energy storage while simultaneously utilizing CO2 resources. The working principle of the Li-CO2 battery cathode involves the electrochemical reaction between CO2 and lithium ions, generating lithium carbonate (Li2CO3) and elemental carbon during discharge, and reversibly decomposing the discharge products during charging. However, during charging and discharging, the wide-bandgap insulator Li2CO3 continuously forms and accumulates on the cathode surface. Due to the high thermodynamic stability and extremely slow decomposition kinetics of Li2CO3, it is difficult to completely decompose during charging, leading not only to the coverage and passivation of the catalytic active sites on the cathode but also to severe polarization and large charge / discharge overpotentials. Furthermore, the kinetics of both the CO2 reduction and precipitation reactions are inert, resulting in low energy efficiency, short cycle life, and poor rate performance. These problems severely restrict the practical application of Li-CO2 batteries.

[0003] The cathode catalyst plays a crucial role in the structure of Li-CO2 batteries. It can lower the energy barrier of CO2 reduction and precipitation reactions, promote the reversible formation and decomposition of the discharge product Li2CO3, and improve the electron conduction and ion transport performance of the cathode. It has been proven that by designing a reasonable cathode catalyst, it is possible to effectively reduce charge-discharge overpotential, improve battery specific capacity and cycle stability. Although noble metal-based catalysts (such as Ru, Ir, Pt, etc.) possess good catalytic activity, their high cost and resource scarcity severely limit their practical application prospects. Therefore, developing low-cost, high-activity non-noble metal cathode catalysts has significant scientific and practical value.

[0004] High-entropy alloys, possessing multi-component synergistic effects and unique entropy-stabilized structures, are used in cathode catalysis, providing abundant and diverse catalytic active sites to effectively adsorb and activate CO2 molecules, accelerating the reversible transformation of discharge products. Composed of five or more metal elements in near equimolar ratios, high-entropy alloys exhibit excellent catalytic activity and structural stability in various electrocatalytic reactions due to their high-entropy effect, lattice distortion effect, slow diffusion effect, and cocktail effect. In recent years, high-entropy alloys have shown significant application potential in the cathode catalysis of Li-CO2 batteries. For example, Sun et al. prepared a NiFeCoCuRu high-entropy alloy catalyst using a liquid-phase co-reduction strategy. Their research showed that the active clusters composed of Ru, Co, and Ni in the alloy can simultaneously stabilize key intermediates in the CO2 reduction reaction, effectively reducing the reaction energy barrier and endowing the catalyst with excellent bidirectional catalytic activity and structural durability. Although the above studies have fully demonstrated the superior performance of high-entropy alloy catalysts in Li-CO2 batteries, the currently reported high-entropy alloy compositions generally contain noble metal elements such as Ru and Ir, resulting in high catalyst costs that are difficult to meet the needs of large-scale practical applications. Therefore, developing high-entropy alloy catalysts composed entirely of non-precious metal elements, while retaining the entropy stabilization effect and the synergistic catalytic advantages of multiple elements, and further reducing material costs, has significant research significance and practical value. Summary of the Invention

[0005] The purpose of this invention is to overcome the technical bottlenecks of Li-CO2 batteries and provide a method for in-situ preparation of carbon nanofiber self-supporting cathode materials loaded with non-precious metal high-entropy alloys via electrospinning. This method uses inexpensive non-precious metal salts and polyacrylonitrile as raw materials, employing electrospinning combined with segmented pre-oxidation and high-temperature carbonization treatment. Simultaneously with the formation of carbon nanofibers, uniformly anchored non-precious metal high-entropy alloy nanoparticles are generated in situ. The resulting self-supporting cathode material requires no additional conductive agents or binders and can be directly used as the cathode for lithium-carbon dioxide batteries, effectively reducing charge-discharge overpotential and improving the battery's specific capacity and cycle stability.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for in-situ preparation of carbon nanofiber self-supported cathode catalysts loaded with non-noble metal high-entropy alloys via electrospinning includes the following steps: Ferric acetate, cobalt acetate, nickel formate, copper chloride, and indium chloride were added to N,N'-dimethylformamide, ultrasonically dispersed, and then polyacrylonitrile was added and stirred overnight to obtain a spinning slurry. The spinning slurry was electrospun to obtain a FeCoNiCuIn@PAN precursor film containing metal salts, which was then vacuum dried for later use. The FeCoNiCuIn@PAN precursor film underwent segmented pre-oxidation treatment in air atmosphere. The pre-oxidized film was then subjected to high-temperature carbonization treatment under Ar / H2 mixed gas protection, causing the polyacrylonitrile to carbonize into carbon nanofibers. Simultaneously, the metal salts were converted in situ into high-entropy alloy nanoparticles (FeCoNiNiCoIn) under carbothermal reduction, which were uniformly anchored in the carbon nanofibers. After cooling, HEA was obtained. FeCoNiCuIn @CNFs self-supporting cathode catalyst.

[0007] Furthermore, the amount of each of the five non-precious metal salts—ferric acetate, cobalt acetate tetrahydrate, nickel formate dihydrate, anhydrous copper chloride, and anhydrous indium chloride—is 0.2 mmol.

[0008] Furthermore, the amount of N,N'-dimethylformamide used is 10 g, the amount of polyacrylonitrile added is 0.8 g, and the molecular weight of polyacrylonitrile is 150,000.

[0009] Furthermore, the electrospinning process parameters are: voltage 20 kV, ambient humidity 50%, temperature 35 ℃, injection rate 10 μL / min, and distance between needle tip and receiver 16 cm.

[0010] Furthermore, the vacuum drying temperature is 60 °C, and the drying time is overnight.

[0011] Furthermore, the specific operation of the segmented heat preservation pre-oxidation treatment is as follows: gradually heating from room temperature to 260 ℃ at a heating rate of 5 ℃ / min, wherein the temperature is kept at 140 ℃, 160 ℃, 180 ℃, 200 ℃, 220 ℃, 240 ℃ and 260 ℃ for 1 hour each.

[0012] Furthermore, the volume ratio of Ar to H2 in the Ar / H2 mixture is 95%:5%.

[0013] Furthermore, the high-temperature carbonization process involves heating to 1000°C at a heating rate of 5°C / min and holding at that temperature for 3 hours.

[0014] Furthermore, the obtained HEA FeCoNiCuIn @CNFs self-supporting cathode catalysts, after being cut into 12 mm diameter discs, can be directly used as the cathode of lithium-carbon dioxide batteries.

[0015] A lithium-carbon dioxide battery comprising HEA obtained by the aforementioned preparation method. FeCoNiCuIn @CNFs self-supporting cathode catalyst.

[0016] This invention utilizes in-situ electrospinning technology to prepare carbon nanofibers as self-supporting cathode catalysts loaded with non-precious metal high-entropy alloys, providing a high-performance cathode material for lithium-carbon dioxide batteries. This material offers the following advantages: (1) This invention is the first to select a combination of five completely non-precious metal elements, namely iron, cobalt, nickel, copper and indium, to prepare a high-entropy alloy / carbon nanofiber self-supporting cathode catalyst in situ by electrospinning. The five metal salts are pre-dispersed uniformly in polymer-spun fibers, and then reduced in situ by high-temperature carbonization to form high-entropy alloy nanoparticles. The particles are uniformly anchored in the carbon nanofiber skeleton, avoiding the problems of easy agglomeration and uneven distribution of nanoparticles in traditional post-loading methods.

[0017] (2) This invention employs a segmented heat preservation and pre-oxidation process, setting multiple heat preservation sections within a temperature range of 140–260 °C. This allows the polyacrylonitrile fibers to undergo sufficient cyclization and cross-linking reactions, forming a stable ladder-shaped polymer structure. This is beneficial for maintaining the fiber morphology and achieving a high carbon yield during subsequent high-temperature carbonization. Simultaneously, the high-temperature carbonization treatment under an Ar / H2 mixed atmosphere promotes the full reduction of metal salts and the interdiffusion between elements, which is conducive to forming a uniform high-entropy alloy solid solution phase.

[0018] (3) HEA prepared in this invention FeCoNiCuIn @CNFs possess a three-dimensional interconnected carbon nanofiber network structure, exhibiting excellent mechanical flexibility and conductivity. They can be directly cut and used as self-supporting positive electrodes without the need for additional conductive agents and binders, simplifying battery assembly processes and improving the overall energy density of the electrode. The high specific surface area and abundant porosity of carbon nanofibers facilitate CO2 gas diffusion and electrolyte wetting, while high-entropy alloy nanoparticles provide abundant multi-site synergistic catalytic active centers, effectively reducing the overpotential of CO2 reduction and precipitation reactions, and improving the specific capacity and cycle stability of lithium-carbon dioxide batteries. Attached Figure Description

[0019] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 The following materials were prepared in Example 1: (a) the spinning precursor FeCoNiCuIn@PAN material and (b) the cathode catalyst HEA. FeCoNiCuIn Physical image of @CNFs material; Figure 2 HEA prepared for Example 1 and Comparative Example 1 FeCoNiCuInXRD powder diffraction patterns of @CNFs and CuIn@CNFs; Figure 3 (a) HEA prepared in Example 1 FeCoNiCuIn SEM images of @CNFs and (b) CuIn@CNFs prepared in Comparative Example 1; Figure 4 HEA prepared in Example 1 FeCoNiCuIn TEM images of @CNFs; (a) 200nm, (b) 50nm; Figure 5 HEA prepared in Example 1 FeCoNiCuIn HAADF-STEM and EDS plots of @CNFs; Figure 6 HEA prepared for Example 1 and Comparative Example 1 FeCoNiCuIn Rate performance graphs of @CNFs and CuIn@CNFs; Figure 7 HEA prepared for Example 1 and Comparative Example 1 FeCoNiCuIn Cyclic performance graphs for @CNFs and CuIn@CNFs. Detailed Implementation

[0020] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention. Example 1

[0021] This embodiment provides a carbon nanofiber material HEA loaded with a non-noble metal high-entropy alloy. FeCoNiCuIn The preparation method of @CNFs self-supporting cathode catalyst includes the following steps: (1) (CH3COO)3Fe (ferric acetate, 0.2 mmol), (CH3COO)2Co·4H2O (cobalt acetate tetrahydrate, 0.2 mmol), Ni(HCOO)2·2H2O (nickel formate dihydrate, 0.2 mmol), CuCl2 (anhydrous copper chloride, 0.2 mmol), and InCl3 (anhydrous indium chloride, 0.2 mmol) were added to 10 g of N,N'-dimethylformamide (DMF) and sonicated for 10 min. Then, 0.8 g of PAN (polyacrylonitrile, Mw 150000) was added, and the mixture was stirred overnight for 12 h to obtain HEA spinning sizing material. The spinning sizing material was then filled into a 10 mL syringe and attached to a syringe pump. A high-voltage power supply was connected to the needle tip. The voltage, humidity, temperature, injection rate, and distance between the needle tip and receiver were set to 20 kV, 50%, 35 ℃, and 10 μL min, respectively. -1 The FeCoNiCuIn@PAN film obtained by electrospinning was placed in a vacuum oven at 60 °C and dried overnight. The FeCoNiCuIn@PAN film prepared in this example is as follows: Figure 1 As shown.

[0022] (2) The polyacrylonitrile film FeCoNiCuIn@PAN loaded with five metal salts was placed in a tube furnace for pre-oxidation at 5 °C min. -1 The heating rate was gradually increased from room temperature to 260 °C, and the temperature was maintained at 140, 160, 180, 200, 220, 240, and 260 °C for 1 hour. After the tubular furnace cooled to room temperature, an Ar / H2 (95%:5% by volume) mixture was introduced at a rate of 5 °C / min. -1 The temperature was increased to 1000 °C and held for 3 h. After cooling to room temperature, the product was collected to obtain HEA. FeCoNiCuIn @CNFs cathode material, HEA prepared in this embodiment FeCoNiCuIn @CNFs materials such as Figure 1 As shown.

[0023] (3) HEA FeCoNiCuIn @CNFs are cut into 12 mm diameter discs using a manual slicer and used directly as the positive electrode of a lithium-carbon dioxide battery.

[0024] A lithium-carbon dioxide battery was assembled as follows: The Li-CO2 battery was prepared in a glove box filled with high-purity argon gas, where the moisture and oxygen levels were maintained below 1.0 ppm. The button cell assembly specifications used in this paper all employed a CR2032 battery case with a hole on one side of the positive electrode. The positive electrode used the positive electrode material prepared above, the negative electrode used a lithium sheet with a diameter of 15.6 mm and a thickness of 0.25 mm, and the separator used a glass fiber membrane with a diameter of 18 mm. A tetraethylene glycol dimethyl ether solution containing 1M lithium bis(trifluoromethanesulfonyl)imide was used as the electrolyte. Finally, the assembled battery was sealed in a self-made glass bottle filled with pure carbon dioxide. The assembled battery was left to stand at room temperature for 24 hours before further testing.

[0025] Comparative Example 1

[0026] This comparative example provides a method for preparing a self-supported cathode catalyst of CuIn@CNFs carbon nanofiber material loaded with copper-indium alloy, specifically including the following steps. (1) CuCl2 (anhydrous copper chloride, 0.2 mmol) and InCl3 (anhydrous indium chloride, 0.2 mmol) were added to 10 g of N,N'-dimethylformamide (DMF) and sonicated for 10 min. Then, 0.8 g of PAN (polyacrylonitrile, Mw 150000) was added, and the mixture was stirred overnight for 12 h to obtain CuIn spinning slurry. The spinning slurry was then filled into a 10 mL syringe and attached to a syringe pump. A high-voltage power supply was connected to the needle tip. The voltage, humidity, temperature, injection rate, and distance between the needle tip and receiver were set to 20 kV, 50%, 35 ℃, and 10 μL min, respectively. -1 The CuIn@PAN film obtained by electrospinning was dried overnight in a vacuum oven at 60 °C. The film was 16 cm thick.

[0027] (2) The polyacrylonitrile film CuIn@PAN loaded with two metal salts was pre-oxidized in a tube furnace at 5 °C for 1 min. -1 The heating rate was gradually increased from room temperature to 260 °C, and the temperature was maintained at 140, 160, 180, 200, 220, 240, and 260 °C for 1 hour. After the tubular furnace cooled to room temperature, an Ar / H2 (95%:5% by volume) mixture was introduced at a rate of 5 °C / min. -1 The temperature was increased to 1000 °C and held for 3 h. After cooling to room temperature, the product was collected to obtain CuIn@CNFs cathode material.

[0028] (3) Cut CuIn@CNFs into 12 mm diameter round slices on a manual slicer and use them directly as the positive electrode of lithium-carbon dioxide batteries.

[0029] A lithium-carbon dioxide battery, the preparation steps of which are the same as those in Example 1.

[0030] The cathode catalysts prepared in Example 1 and Comparative Example 1 were used in lithium carbon dioxide batteries and tested and characterized.

[0031] Material characterization Figure 1 The FeCoNiCuIn@PAN thin film (a) and HEA prepared in Example 1 are shown. FeCoNiCuIn Optical photograph of the @CNFs cathode catalyst material (b). Figure 2 The X-ray diffraction patterns of the cathode catalyst materials in Example 1 and Comparative Example 1 are shown. HEA FeCoNiCuIn The main diffraction peaks of @CNFs and CuIn@CNFs are roughly consistent with the main diffraction peaks in the Cu standard PDF card. However, due to the influence of lattice distortion, the diffraction peaks of both have shifted, indicating that other metal atoms diffuse into the Cu lattice during the thermal reduction process, forming an FCC single-phase solid solution. Figure 3 SEM images of the cathode catalyst materials of Example 1 and Comparative Example 1, HEA FeCoNiCuIn Both @CNFs and CuIn@CNFs are uniformly distributed fiber networks. This interconnected network structure not only provides sufficient surface area for the loading of metal particles, but also provides an efficient conductive path for charge transport in subsequent applications. Figure 4 This is a TEM image of Example 1, HEA FeCoNiCuIn @CNFs contain a large number of ultrafine nano-metal particles in their carbon nanofiber matrix. Figure 5 The HAADF-STEM and EDS images for Example 1 show that five metals, Fe, Co, Ni, Cu, and In, are uniformly dispersed in HEA. FeCoNiCuIn In @CNFs, the high-entropy alloy HEA is explained. FeCoNiCuIn Synthesis successful.

[0032] Ratio Performance Test The HEA obtained in Example 1 FeCoNiCuIn The rate performance of Li-CO2 batteries assembled with @CNFs cathode catalyst and CuIn@CNFs cathode catalyst prepared in Comparative Example 1 were tested. Figure 6 It can be concluded that the CuIn@CNFs cathode catalyst battery operates at 10, 20, 40, 60, 80, 100, 150, and 200 μA cm⁻¹. -2 The discharge potential decays drastically at current densities up to a maximum of 200 μA cm⁻¹. -2 It reached an ultra-high overpotential of 3.30V; while HEA FeCoNiCuIn@CNFs cathode catalyst cells at 10, 20, 40, 60, 80, 100, 150 and 200 μA cm⁻¹ -2 The discharge potential did not show a very large potential decay at the current density, even at the maximum current density of 200 μA cm⁻¹. -2 The overpotential remained at 1.49 V, indicating that the non-noble metal high-entropy alloy HEA... FeCoNiCuIn @CNFs cathode catalyst batteries exhibit good rate performance.

[0033] Cyclic performance test The HEA obtained in Example 1 FeCoNiCuIn Li-CO2 batteries assembled with @CNFs cathode catalyst and CuIn@CNFs cathode catalyst prepared in Comparative Example 1, respectively, were subjected to cycle performance tests. Figure 7 It can be concluded that the CuIn@CNFs cathode catalyst battery, after 1250 hours of cycling, at 20 μA cm⁻¹ -2 Current density and 100 μAh cm -2 Under rated capacity conditions, after 114 cycles, its discharge voltage experienced a sharp drop, falling to approximately 2.33 V. As the cycling progressed to 800 hours, the discharge voltage continued to decrease, approaching 2 V, while the overpotential continued to increase, ultimately leading to complete failure after 1250 hours. Meanwhile, the HEA... FeCoNiCuIn The @CNFs cathode catalyst battery maintained stable charge and discharge under the same conditions for over 1300 hours of cycling, with the overpotential consistently remaining below 1 V, and could cycle stably for more than 1300 hours. This indicates that HEA FeCoNiCuIn @CNFs cathode catalysts have successfully achieved a synergistic improvement in activity and stability in Li-CO2 batteries.

[0034] Based on the analysis of the above test results, the lithium-carbon dioxide battery assembled using the technical solution of this invention has high cycle stability and good rate performance, indicating that this solution can effectively catalyze the redox kinetics of CO2 in lithium-carbon dioxide batteries.

[0035] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing an in-situ supported carbon nanofiber catalyst of a non-noble metal high-entropy alloy, characterized in that, Includes the following steps: Step 1: Add non-precious metal salts to N,N'-dimethylformamide, disperse by ultrasonication, add polyacrylonitrile, and stir overnight to obtain spinning slurry; Step 2: The spinning slurry obtained in Step 1 is assembled into a syringe and installed into an electrospinning device for spinning to obtain a FeCoNiCuIn@PAN precursor film containing non-precious metal salts, which is then vacuum dried for later use. Step 3: The FeCoNiCuIn@PAN precursor film obtained in Step 2 is subjected to segmented heat preservation pre-oxidation treatment in an air atmosphere; Step 4: The pre-oxidized film from Step 3 is subjected to high-temperature carbonization under Ar / H2 mixed gas protection to carbonize polyacrylonitrile into carbon nanofibers. At the same time, the metal salt is converted into a high-entropy alloy in situ under carbothermic reduction and uniformly anchored in the carbon nanofibers. After cooling, a carbon nanofiber catalyst loaded with a non-precious metal high-entropy alloy is obtained.

2. The method as described in claim 1, characterized in that, The non-precious metal salts added in step 1 are: ferric acetate, cobalt acetate tetrahydrate, nickel formate dihydrate, anhydrous copper chloride, and anhydrous indium chloride. The amount of each of these five non-precious metal salts is 0.2 mmol.

3. The method as described in claim 1, characterized in that, In step 1, the amount of N,N'-dimethylformamide used is 10 g, the amount of polyacrylonitrile added is 0.8 g, and the molecular weight of polyacrylonitrile is 150,000.

4. The method as described in claim 1, characterized in that, The electrospinning process parameters in step 2 are: voltage 20kV, ambient humidity 50%, temperature 35 ℃, injection rate 10 μL / min, and distance between needle tip and receiver 16 cm.

5. The method as described in claim 1, characterized in that, In step 2, the vacuum drying temperature is 60 ℃, and the drying time is overnight.

6. The method as described in claim 1, characterized in that, The specific operation of the segmented heat preservation pre-oxidation treatment in step 3 includes: gradually heating from room temperature to 260 ℃ at a heating rate of 5 ℃ / min, and holding at 140 ℃, 160 ℃, 180 ℃, 200 ℃, 220 ℃, 240 ℃ and 260 ℃ for 1 hour each.

7. The method as described in claim 1, characterized in that, In step 4, the volume ratio of Ar to H2 in the Ar / H2 mixture is 95%:5%.

8. The method as described in claim 1, characterized in that, The high-temperature carbonization process in step 4 includes heating to 1000 ℃ at a heating rate of 5 ℃ / min and holding at that temperature for 3 hours.

9. A method for preparing a lithium-carbon dioxide battery cathode, characterized in that, The carbon nanofiber catalyst supported on a non-precious metal high-entropy alloy, prepared by any one of claims 1 to 8, is cut into discs with a diameter of 12 mm and used directly as the positive electrode of a lithium-carbon dioxide battery.

10. A lithium-carbon dioxide battery comprising a catalyst obtained by the preparation method according to any one of claims 1 to 8.